Isorhamnetin Enhances the Radiosensitivity of A549 Cells Through Interleukin-13 and the NF-κB Signaling Pathway - Du, Yarong; Jia, Cong; Liu, Yan; Li, Yehua; Wang, Jufang; Sun, Kun (Frontiers in Pharmacology, 2021)
Isorhamnetin (ISO), a naturally occurring plant flavonoid, is widely used a phytomedicine. The major treatment modality for non-small-cell lung carcinoma (NSCLC) is radiotherapy. However, radiotherapy can induce radioresistance in cancer cells, thereby resulting in a poor response rate. Our results demonstrated that pretreatment with ISO induced radiosensitizing effect in A549 cells using colony formation, micronucleus and H2AX foci assays. In addition, ISO pretreatment significantly enhanced the radiation-induced the incidence of apoptosis, the collapse of MMP and the expressions of proteins associated with cellular apoptosis, as well as suppressed the upregulation of NF-Bp65 induced by IR in A549 cells. Interestingly, the expression of IL-13, an anti-inflammatory cytokine, was positively correlated with the ISO-mediated radiosensitization of A549 cells. The knockdown of IL-13 expression by RNA interference decreased the IL-13 level, and thus, reduced ISO-mediated radiosensitivity in cells. We also found that the IR-induced NF-B signaling activation was inhibited by ISO pretreatment, and it was abrogated in IL-13 silenced cells. We speculated that ISO may confer radiosensitivity on A549 cells via increasing the expression of IL-13 and inhibiting the activation of NF-B. To our knowledge, this is the first report demonstrating the effects of ISO treatment on the responsiveness of lung cancer cells to irradiation through IL-13 and the NF-B signaling pathway. In summary, ISO is a naturally occurring radiosensitizer with a potential application in adjuvant radiotherapy.